CARE AS A PRODUCT OF MULTIPLE HUMAN INTERACTIONS:"CARING ABOUT THE OTHER" - Patricia Klock; Anna Carolina Ribeiro Lopes Rodrigues; Dirce Stein Backes; AAlacoque Lorenzini Erdmann (Universidade Federal do Paraná, 2007)
This qualitative study aimed to apprehend the meaning of nursing care as the product of multiple human interactionswithin the context of hospital nursing care. The Grounded Theory was used as a methodological referential. Data collection was carriedout through a semi-structured interview with eighteen informants, being six nurses, six nursing technicians and six relatives of admittedpatients encompassing three sample groups. Data analysis was performed up to the Theoretical Codification, leading to the identificationof the conceptual category "caring about the other", representative of the nursing meaning as the product of multiple human interactionsthat broadens the dimension of care beyond non-flexible and mechanical practices evolving from the excessive order and routinedetermined by the traditional doing.